Aquinas’ Counterfactual Incarnations - Conn, Christopher Hughes (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
This paper is an examination of Aquinas’ account of the various ways in which the Incarnation might have occurred. Aquinas maintains that the Son of God became incarnate by assuming a specific body/soul union. Although he maintains that it was fitting for God to have become incarnate in this manner, he contends (i) that any one of the three divine persons could have become incarnate in this manner, (ii) that any plurality of these Persons could have assumed the same body/soul union, (iii) that any plurality of these Persons could have assumed distinct body/soul unions, and (iv) that any of the divine persons could have assumed a plurality of body/soul unions. Given the increasingly bizarre nature of these scenarios, it is worth asking, first, whether Aquinas is rationally entitled to these modal judgments, and second, why he is advancing them so early in his Discourse on the Incarnation in the Summa theologiae. In this paper I contend, first, that these counterfactual scenarios are possible if his actual account is possible; and second, that these scenarios they shed light (i) on the manner in which the Son of God did become incarnate, (ii) on the nature and scope of God’s freedom, love and power, and (iii) on Aquinas’ relationship with Rahner’s Rule, viz., the thesis that the economic Trinity is identical with the immanent Trinity.